Leadership Without Easy Answers - Heifetz, Ronald A. (Cambridge Belknap Press of Harvard University Press, 1994)
The economy uncertain, education in decline, cities under siege, crime and poverty spiraling upward, international relations roiling: we look to leaders for solutions, and when they dont deliver, we simply add their failure to our list of woes. In doing so, we do them and ourselves a grave disservice. We are indeed facing an unprecendented crisis of leadership, Ronald Heifetz avows, but it stems as much from any leader's inability to meet them. His book gets at both of these problems, offering a practical approach to leadership for those who lead as well as those who look to them for answers. Fitting the theory and practice of leadership to our extraordinary times, the book promotes a new social contract, a revitalization of our civic life just when we most desperately need it. Drawing on a dozen years of research among managers, officers, and politicians in the public realm and the private sector, among the nonprofits, and in teaching, Heifetz presents clear, concrete prescriptions for anyone who needs to take the lead in almost any situation, under almost any organizational conditions, no matter who's in charge. Hisstrategy of leadership applies not only to people at the top but also to those who must lead without authority-activists as well as presidents, managers as well as workers on the frontline. Here are lyndon Johnson, Martin Luther King Jr., and Mahatma Gandhi, in triumph and in tragedy. Here too are military officers and soldiers, doctors and patients, college students, and local civic groups. Sketched with precision, touched by empathy, and unfailingly interesting, this cast of characters brings Heifetz's theory to life, demonstrating what a practitioner can do-or avoid doing-to assume leadership in an age without easy answers
Includes bibliographical references (p. 279-337)
Keywords: Leadership